COMPARING THE URDU VERSION OF STRENGTH AND DIFFICULTIES QUESTIONNAIRE (SDQ) AND THE CHILD BEHAVIOR CHECKLIST (CBCL) IN A SAMPLE OF 5-11 YEAR OLD SCHOOL CHILDREN IN KARACHI, PAKISTAN - Syed, Ehsan Ullah (Journal of Pakistan Psychiatric Society, 2007)
Objectives: This study aims to compare two widely used instruments in child mental health research, the Strength and Difficulties Questionnaire (SDQ) is a brief behavioral screening questionnaire that can be completed in about 5 minutes by the parents and teachers of 4-16 year olds. Design: Cross sectional and correlation study Place and duration of study: This study was conducted in schools of Karachi between January to June 2006. Subjects and Method: The Urdu version of SDQ has been translated and was downloaded from the website (www.sdqinfro.com), the SDQ has been validated in Pakistan. The CBCL was translated by a team of expert through a rigorous seven step process of translation. Both the SDQ and CBCL were completed by 556 parents of school children aged 5-11 attending schools in various towns of Karachi. Results: Given the non normal nature of some of the distributions , correlations were calculated using Spearman’s rho co efficient. Scores from the SDQ and CBCL were moderately corelated and equally able to screen out children with emotional and behavioral problems. SDQ had a certain advantage over CBCL as it is much shorter and can be completed in much lesser time than the longer CBCL. Conclusion: The study shows that like the original English version and other similar studies , the SDQUrdu and the Urdu CBCL are equally valuable tools for the most clinical and research purpose. Key words: Child Psychopathology, Psychometrics, questionnaires, Pakistan.